2001
DOI: 10.1053/eupc.2001.0160
|View full text |Cite
|
Sign up to set email alerts
|

Atrial arrhythmia suppression by atrial overdrive pacing: pacemaker Holter assessment

Abstract: The purpose of this study was to assess the efficacy of overdrive, single-site right atrial appendage pacing to reduce the burden of atrial fibrillation (AF) when compared with a standard lower rate limit of 60 bpm. This was verified by using the pacemaker's Holter. Eighteen subjects with a pre-implant history of paroxysmal AF and implanted DDDR mode-switching pacemakers were recruited. The pacemaker lower rate limit was programmed in random order to 60, 75 or 90 bpm for three 2-month periods and the amount of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…The maximum overdrive rate in our study ranged between 100 and 160 beats/min, different from maximum rates of 80–120 beats/min, 5 or rates fixed at 120 beats/min in other studies 4 , 8 . Despite this diversity of settings, no study examined the influence of the selected values, except for basic rate, 9,10 on the clinical effects of overdrive therapy.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The maximum overdrive rate in our study ranged between 100 and 160 beats/min, different from maximum rates of 80–120 beats/min, 5 or rates fixed at 120 beats/min in other studies 4 , 8 . Despite this diversity of settings, no study examined the influence of the selected values, except for basic rate, 9,10 on the clinical effects of overdrive therapy.…”
Section: Discussionmentioning
confidence: 57%
“…The use of a high basic rate to overdrive the atrium was associated prominent patient discomfort. Ward et al 10 reported that one third of patients failed to tolerate DDDR pacing at a basic rate of 90 beats/min.…”
Section: Discussionmentioning
confidence: 99%
“…In a pilot study, overdrive atrial pacing limited the number of atrial ectopic events; however, was underpowered to detect a difference in the number of AF episodes 5 . In recent studies, AMS episodes and measures of functional status were similar in patients treated consecutively with standard versus overdrive pacing, 6–8 whereas preliminary results from the consistent atrial pacing (CAP) and the prevention by overdriving (PROVE) trials found that overdrive pacing reduced the incidence of AF 9,10 . The atrial algorithm we used was already tested in the Atrial Dynamic Overdrive Pacing Trial (ADOPT) 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, pacing at a certain rate will probably not be effective in the prevention of AF onset, as also suggested by some clinical data. 57,58 With regard to APB's characteristics, there are three principal situations that initiate AF. Most often, AF is initiated by a closely coupled APB.…”
Section: Changes In the Sinus Rhythm Rate And Apb Prematuritymentioning
confidence: 99%